Factors that affect the English language teaching - learning process in Ecuadorian public high schools, estudio realizado en las siguientes instituciones educativas: Colegio Provincia de Pastaza, Nuestra Señora de Pompeya, Instituto Superior Tecnológico Francisco de Orellana, Vicente Ferrer y 12 de Mayo en la ciudad de Puyo, provincia de Pastaza durante el año lectivo 2012 - 2013 - Alvarado Vera, Javier Alfonso (2013)
The topic of this research is “Factors that affect the English language teaching -learning process in Ecuadorian public high schools”, and its purpose was to analyze the factors that affect the English language teaching-learning process. This project was developed in five public high schools in Puyo city, Pastaza province, Ecuador. The method used for this study was quantitative, through class observation sheets and questionnaires applied to teachers and students in fifteen observed English classes. The sample included two classes of 9th year, two classes of 10th year, five classes of first year of Bachillerato, four classes of second year of Bachillerato and two classes of third year of Bachillerato. The aspects considered in carrying out the analysis come from the information obtained in the observed classes and teachers and students’questionnaire, being demonstrated in charts and graphics of the surveys previously applied. The main conclusion from the analysis showed that the major factors that affect the English language teaching-learning process are the use of few methods and techniques applied by the teachers, and the limited use of English teaching resources in the classroom.